Studies of ice-forming agent propagation in the boundary layer of the atmosphere under the action of ground-based NAG-07M aerosol generators - Andrej Mikhailovitch Petrunin; Viktor Petrovich Korneev; Boris Pavlovich Koloskov; Andrej Viktorovich Chastukhin; Aleksej Aleksandrovich Bychkov; Nikolaj Sergeevich Kim; Boris Nikolaevich Sergeev (Наука. Инновации. Технологии)
The paper describes the technical means, methods and results of experimental studies of the spread of ice-forming agent in the boundary layer of the atmosphere under the action of ground-based aerosol generator NAG-07M. Comparison of the data on sampling by an AVA 3-240-01S probe mounted aboard Vilga-35A aircraft with aerosol propagation calculations using a 3-D SeedDisp model, shows: 1. The concentration of silver iodide measured in the atmosphere was above background one to a height of 1200 m at distances of 3 to 9 km from the place of the generator installation. 2. The developed «SeedDisp» numerical model in general qualitatively correctly describes the distribution of silver iodide aerosols in the boundary layer and the free atmosphere under the action of ground-based aerosol generator NAG-07M. Thus, the coefficient of correlation of the measured and calculated by model values of the silver iodide particles concentration in sub-cloud layer exceeded the value of 0,7.